Faktor Kepatuhan Pekerja pada Kawasan Tanpa Rokok (KTR) Di PT. PAL Indonesia (PERSERO) - Rizka Fitria Fajrin (Universitas Airlangga, 2019)
Background: The workplace is every room where the workers work with various sources of danger. Hazards that can occur include fire, work accidents and occupational diseases. Fire may occur due to electrical short circuit, human negligence and ignition of flammable liquids and gases. Workers who throw cigarettes carelessly become a trigger of fire and even blasting at work. Therefore, the government made a policy on restrictions on the use of cigarettes in the workplace, the Non-Smoking Area. Although regulations relating to non-smoking areas have been established and legalized, there are still non-smoking area violations. PT. PAL Indonesia (Persero) has had regulations related to non-smoking areas that have been applied in the company. But in some places still found cigarette butts are scattered. This indicates that there are still workers who smoke indiscriminately and do not throw cigarette butts to the proper place. Purpose: The purpose of this study is to analyze factors relates to non-smoking area adherence at PT. PAL Indonesia (Persero) in terms of Milgram's Obedience theory. Methods: The method in this research is analytic observational with a quantitative approach and cross-sectional research design. Results: The results of this study indicate that factors related to obedience of non-smoking area are personal responsibility with a significant value of 0,031 (p<0,05). Conclusion: Workers at PT. PAL Indonesia (Persero) has good obedience to non-smoking area in terms of personal responsibility.